Peningkatan Pengetahuan, Ketrampilan dan Kapasitas Peternak Kambing Domba dalam Penyediaan Pakan Ternak Berkualitas - Enike Dwi Kusumawati; Akhmad Zaini; Endi Sarwoko; Ali Mahmud; Kinta Ramayanti (Jurnal Pemberdayaan Masyarakat, 2024)
The priority problem for goat and sheep breeders in Wagir District, Malang Regency is the low ability to process animal feed. Therefore, it is necessary to transfer knowledge and feed technology to increase the capacity of breeders in providing quality feed. The method used in this service activity is a participatory action and learning system approach which includes Focus Group Discussions, training and demonstration of feed fermentation technology, mentoring and field monitoring of the results of fermented feed technology transfer in 12 villages. The results of the activity showed a significant increase in awareness, knowledge and skills of sheep and goat breeders in processing fermented feed based on local resources. All feed can be provided independently (100%). Utilization of local resources in providing quality animal feed for sheep and goats is at least 85% so this also has an impact on increasing farmers' income because the use of feed is more efficient and effective. Community service activities have been running very well and successfully with the support and cooperation of all partners and breeders in Wagir District and Malang Regency. This good cooperation needs to be maintained and further improved.